A practical guide for the husbandry of cave and surface invertebrates as the first step in establishing new model organisms. - Marko Lukić; Lada Jovović; Jana Bedek; Magdalena Grgić; Nikolina Kuharić; Tin Rožman; Iva Čupić; Bob Weck; Daniel Fong; Helena Bilandžija (PLoS ONE, 2024)
While extensive research on traditional model species has significantly advanced the biological sciences, the ongoing search for new model organisms is essential to tackle contemporary challenges such as human diseases or climate change, and fundamental phenomena including adaptation or speciation. Recent methodological advances such as next-generation sequencing, gene editing, and imaging are widely applicable and have simplified the selection of species with specific traits from the wild. However, a critical milestone in this endeavor remains the successful cultivation of selected species. A historically overlooked but increasingly recognized group of non-model organisms are cave dwellers. These unique animals offer invaluable insights into the genetic basis of human diseases like eye degeneration, metabolic and neurological disorders, and basic evolutionary principles and the origin of adaptive phenotypes. However, to take advantage of the beneficial traits of cave-dwelling animals, laboratory cultures must be established-a practice that remains extremely rare except for the cavefish Astyanax mexicanus. For most cave-dwelling organisms, there are no published culturing protocols. In this study, we present the results of our multi-year effort to establish laboratory cultures for a variety of invertebrate groups. We have developed comprehensive protocols for housing, feeding, and husbandry of cave dwellers and their surface relatives. Our recommendations are versatile and can be applied to a wide range of species. Hopefully our efforts will facilitate the establishment of new laboratory animal facilities for cave-dwelling organisms and encourage their greater use in experimental biology.